Complete vs. incomplete percutaneous revascularization in patients with chronic total coronary artery occlusion - Maestre-Luque, Luis Carlos; Gonzalez-Manzanares, Rafael; Suárez de Lezo, Javier; Hidalgo, Francisco; Barreiro-Mesa, Lucas; de Juan, Jaime; Gallo, Ignacio; Perea, Jorge; Alvarado, Marco; Romero, Miguel; Ojeda, Soledad; Pan, Manuel (Frontiers in Cardiovascular Medicine, 2024)
Introduction There is current controversy surrounding the benefits of percutaneous coronary intervention (PCI) of chronic total coronary occlusions (CTO). We aimed to evaluate the impact of complete percutaneous revascularization on major adverse cardiovascular events (MACE) in patients with CTO. Methods A retrospective observational study was conducted of consecutive patients referred for invasive coronary angiography at a single center between January 2018 and December 2019 and at least a CTO. The patients were divided into two groups according to the result of the procedure: complete revascularization of CTO (CR-CTO) versus incomplete revascularization (ICR-CTO) (patients with at least one non-recanalized CTO). Short- and mid-term clinical outcomes were evaluated. The primary endpoint was a composite of MACE that included all-cause death, non-fatal myocardial infarction, non-fatal stroke, or unplanned revascularization. Results In total, 359 patients with CTO were included. The median age was 68 years [interquartile range (IQR) 60–77 years], 66 (18%) were women and 169 (47.3%) had diabetes mellitus. In all, 167 (46.5%) patients received complete revascularization. After a median follow-up of 42 months (IQR 46–50 months), the primary endpoint occurred in 39 (23.4%) patients in the CR-CTO group and in 75 (39.1%) in the ICR-CTO group (HR 0.50, 95% CI 0.34–0.74; p < 0.001). This association remained significant in an inverse probability weighted model considering prognostic factors (adjusted HR 0.61, 95% CI 0.41–0.92; p = 0.018) and was driven by lower rates of all-cause death (adjusted OR 0.50, 95% CI 0.23–0.84; p = 0.01). Conclusions Complete revascularization of CTO was associated with a lower risk of MACE in the midterm follow up.